The Model of Disadvantages? The Choice-of-Law Provisions of the Commonwealth of Independent States Model Civil Code and Their Impact on National Legislations - Yeshniyazov, N. (Hungarian Journal of Legal Studies 57, No 4, pp. 427–446, 2016)
The article describes the distinctive features and main disadvantages of the Commonwealth of Independent States Model Civil Code’s provisions of general parts of private international law, which found reception in the national legislation of the member states. The Code was accepted as a model for codification by the majority of the CIS states. An analysis of the Code’s provisions can help interpret the unclear national rules, will allow to predict courts’ modus operandi in conflict-of-laws cases and can provide an opportunity to estimate further development prospects of private international law in the post-Soviet area.
Keywords: Commonwealth of Independent States; Model Civil Code; private international law; choice of law; codification; application of conflict rules; application of foreign law